The long term effect of pulmonary tuberculosis on income and employment in a low income, urban setting - Meghji, Jamilah (Thorax, 2021)
BACKGROUND: Mitigating the socioeconomic impact of tuberculosis (TB) is key to the WHO End TB Strategy. However, little known about socioeconomic well-being beyond TB-treatment completion. In this mixed-methods study, we describe socioeconomic outcomes after TB-disease in urban Blantyre, Malawi, and explore pathways and barriers to financial recovery. METHODS: Adults ≥15 years successfully completing treatment for a first episode of pulmonary TB under the National TB Control Programme were prospectively followed up for 12 months. Socioeconomic, income, occupation, health seeking and cost data were collected. Determinants and impacts of ongoing financial hardship were explored through illness narrative interviews with purposively selected participants. RESULTS: 405 participants were recruited from February 2016 to April 2017. Median age was 35 years (IQR: 28–41), 67.9% (275/405) were male, and 60.6% (244/405) were HIV-positive. Employment and incomes were lowest at TB-treatment completion, with limited recovery in the following year: fewer people were in paid work (63.0% (232/368) vs 72.4% (293/405), p=0.006), median incomes were lower (US$44.13 (IQR: US$0–US$106.15) vs US$72.20 (IQR: US$26.71–US$173.29), p<0.001), and more patients were living in poverty (earning <US$1.90/day: 57.7% (211/366) vs 41.6% (166/399), p<0.001) 1 year after TB-treatment completion compared with before TB-disease onset. Half of the participants (50.5%, 184/368) reported ongoing dissaving (use of savings, selling assets, borrowing money) and 9.5% (35/368) reported school interruptions in the year after TB-treatment completion. Twenty-one participants completed in-depth interviews. Reported barriers to economic recovery included financial insecurity, challenges rebuilding business relationships, residual physical morbidity and stigma. CONCLUSIONS: TB-affected households remain economically vulnerable even after TB-treatment completion, with limited recovery in income and employment, persistent financial strain requiring dissaving, and ongoing school interruptions. Measures of the economic impact of TB disease should include the post-TB period. Interventions to protect the long-term health and livelihoods of TB survivors must be explored.